A Cidade dos invisíveis? Indígenas e impactos de políticas neodesenvolvimentistas em Altamira, sudoeste paraense - CARDOSO, Suelem Maciel (Universidade Federal do Pará, 2019)
From an interdisciplinary perspective, this research meets the theme "indigenous people in cities of large projects". Analyzing the presence and meaning of indigenous peoples in the middle city of Altamira in the context of large Amazonian projects, associated with the neodevelopment model, in the most recent period, is its main objective. In this sense, the urban space is our focus of empirical analysis, being the target of many public and private policies conflicting with the ways of life of a city with a strong link with the Xingu River. To systematize the research, we use the following methodological procedures: a) theoretical-conceptual bibliographic review of themes pertinent to the research; b) historical-geographic revision on the socio-spatial formation of the city of Altamira; c) survey of primary and secondary data on indigenous peoples in the city of Altamira and their ways of life, as well as their significance in the context of urban and regional development policies and the mitigation and compensation of impacts of the Belo Monte Hydroelectric Power Plant; d) individual recorded interviews with semi-structured questions. With the implementation of the Belo Monte Hydroelectric Power Plant, in the sub-region of the Southwest of paraense and the middle course of the Xingu River, in the scope of neo-developmental policies, many rights of the Xingu-indigenous peoples have been violated. From the enterprise, the movement for rights struggle and specific policies for this differentiated population was increased, especially in the intra-urban space of Altamira, which was reflected in the increase in the number of indigenous organizations and their associates in the city. The set of policies designed for the region and the city to develop and mitigate or compensate for impacts of the Belo Monte Hydroelectric Power Plant, despite the fact that their diagnoses are attentive to some particularities, such as the indigenous presence and their way of life, has not been taken into account